#FeesMustFall as social movement and emancipatory politics? Moving towards an apocalyptic theological praxis outside the limits of party politics - Buttelli, Felipe G. K. (HTS teologiese studies, 2017)
This article proposes three reflexive movements. The first one offers an introduction to Fees Must Fall, pointing to some aspects that allow us to understand it as a social movement and some of its basic features. The second movement is a theoretical one, constructing the notion of emancipatory politics. It is based on the distinctions suggested by Jacques Rancière between ‘police and politics’ and by Michael Neocosmos between ‘excessive and expressive’ politics. It will also present the Freirean notion of ‘conscientisation and dialogicity’, emphasising the learning experience from the political praxis within emancipatory social movements. The third movement offers, as conclusion, an apocalyptic politics as suggested by Žižek, envisioned through the lens of Christian eschatology, as a critical approach to social movements towards the radical transformation of society.